The industrial progress of Belgium: an object lesson for Ireland - Dawson, Charles (Statistical and Social Inquiry Society of Ireland, 1912)
The recent perusal of two very interesting works on the present industrial position of Belgium suggested to me to select the above subject for this paper. The works are "Land and Labour Lessons from Belgium," by Mr. B. Seebohn Rowntree, and "La Belgique au Travail," by M. J. Izart, published in Paris in 1910. However, before dealing with the present state of affairs, it will be interesting and useful to glance at the industrial position of the country before the Revolution of 1830.
Read May 14th, 1912
Keywords: Industry, Belgium; Economic progress; 314.15